Looking back while moving forward: How past responses to climate change can inform future adaptation and mitigation strategies in the Arctic. (30th May 2020) - Desjardins, Sean P.A.; Friesen, T. Max; Jordan, Peter D.
Abstract: Modern Arctic Indigenous peoples face many interconnected pressures, not the least of which is anthropogenic climate change, which is emerging as one of the most dramatic drivers of social and economic change in recent memory. In this paper, we investigate whether or not insights into premodern strategies for coping with climate change—and especially the "deeper histories" of traditional ways-of-knowing—can play a useful role in future planning, management and mitigation efforts. We do this in two ways. First, we assess this special issue's 17 archaeological case studies, in order to determine whether they are conducted within a framework that is consistent with approaches to resilience in studies of modern Arctic communities. Second, we focus on three climate-driven challenges faced by Canadian Arctic Inuit: safe travel, food security and food safety. For each, we identify specific ways in which studies of past social-ecological systems intersect with modern climate adaptation. We conclude that since archaeological insights highlight the operation of decision-making processes within long-term culture-adaptive trajectories, they can offer unique insights into the much shorter-term processes currently underway. While we highlight many potential directions for productive collaboration, much more work is required in local and regional settings to demonstrate the full potential of archaeology for future-oriented planning and mitigation efforts.